2009
DOI: 10.1165/rcmb.2008-0331oc
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility Group Box 1 Contributes to Lethality of Endotoxemia in Heme Oxygenase-1–Deficient Mice

Abstract: High-mobility group box 1 (HMGB1) is a nuclear protein that has been found to be a critical mediator of lethality in endotoxemia and sepsis. During the systemic inflammatory response, circulating levels of HMGB1 are increased, but in a delayed fashion compared with early inflammatory mediators. To counteract the inflammatory response of endotoxemia, a secondary anti-inflammatory response ensues in an attempt to prevent inflammation-induced tissue injury. One such cytoprotective gene that is induced during endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 48 publications
(56 reference statements)
7
37
0
Order By: Relevance
“…Moreover, delayed administration of CORM-2 (12 h after LPS or CLP) significantly inhibited HMGB1 levels without alterations in serum levels of TNF-␣ or IL-1␤, suggesting that inhibition of HMGB1 is a clue for HO-1 and/or COmediated improved survival. Consistent with a recent report that CORM-2 was able to suppress the increased circulating HMGB1 in HO-1(Ϫ/Ϫ) mice and rescued HO-1(Ϫ/Ϫ) mice from the lethality of endotoxemia (Takamiya et al, 2008), the finding of reduced serum levels of HMGB1 by CO and/or HO-1 inducers implies that CO is important regulator of HMGB1 release. However, they (Takamiya et al, 2008) Fig.…”
Section: Co Inhibits Hmgb1 Release In Lps-and Clp-induced Sepsis 179supporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, delayed administration of CORM-2 (12 h after LPS or CLP) significantly inhibited HMGB1 levels without alterations in serum levels of TNF-␣ or IL-1␤, suggesting that inhibition of HMGB1 is a clue for HO-1 and/or COmediated improved survival. Consistent with a recent report that CORM-2 was able to suppress the increased circulating HMGB1 in HO-1(Ϫ/Ϫ) mice and rescued HO-1(Ϫ/Ϫ) mice from the lethality of endotoxemia (Takamiya et al, 2008), the finding of reduced serum levels of HMGB1 by CO and/or HO-1 inducers implies that CO is important regulator of HMGB1 release. However, they (Takamiya et al, 2008) Fig.…”
Section: Co Inhibits Hmgb1 Release In Lps-and Clp-induced Sepsis 179supporting
confidence: 90%
“…Consistent with a recent report that CORM-2 was able to suppress the increased circulating HMGB1 in HO-1(Ϫ/Ϫ) mice and rescued HO-1(Ϫ/Ϫ) mice from the lethality of endotoxemia (Takamiya et al, 2008), the finding of reduced serum levels of HMGB1 by CO and/or HO-1 inducers implies that CO is important regulator of HMGB1 release. However, they (Takamiya et al, 2008) Fig. 10.…”
Section: Co Inhibits Hmgb1 Release In Lps-and Clp-induced Sepsis 179supporting
confidence: 90%
See 2 more Smart Citations
“…73 A recent study demonstrated that high-mobility group box 1 contributes to lethality of endotoxemia in HO-1-deficient mice. 74 A significant reduction of high-mobility group box 1 was noted after administration of carbon monoxide and biliverdin, products of the HO-1 enzymatic pathway. Moreover, HO-1 suppresses the infiltration of neutrophils in rat liver during sepsis.…”
Section: Therapeutic Options For the Present And Futurementioning
confidence: 97%